Pemulihan Sebagai Bukti Kekuasaan YHWH: Klasifikasi Ucapan Ilahi Terhadap Frasa "Hari TUHAN" Menurut Yoel 2:31, Zakharia 14:1, Maleakhi 4:5 - Kiamani, Andris; Sualang, Farel Yosua (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2025)
This study aims to explore intertextually the true meaning of the phrase "the day of the LORD" according to Joel 2:31; Zechariah 14:1 and Malachi 4:5. Some studies emphasize different meanings such as miracles that serve as signs, the day of judgment, the day of Jesus' life, and the second coming of Jesus. It also includes a day of remembrance to sinful mankind. The diverse interpretations of the phrase "day of the LORD" in the Old Testament create a significant research gap. This condition is caused by the absence of researchers who look directly at the three books from the point of view of the alignment of the phrase "day of the LORD". The method used is the hermeneutic approach of prophetic literature. Thus this paper finds the meaning of the phrase "the day of the LORD" according to Joel 2:31; Zechariah 14:1; Malachi 4:5, based on the classification of divine utterances by prophets there are parallels in meaning that emphasize a special day in the future as a marker of important future events that show the power of YHWH (the LORD) as the only ruler of the universe to provide deliverance and restoration to His people.